SCHOOLS OF EDUCATION IN THE EDUCATIONAL PERSPECTIVE OF AXIOLOGY - Afryansyah Afry Afryansyah; Sumarni Sumarni; Ria S Wahyuni; Ratu Wardarita; Puspa I Utami (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
The aimed of the study was to describe the education genre in educational axiology sight/ perspective. To reach the aim of the study, the writer has done the research study/ literature research within various of book sources and scientific journal. Based on the literature study, it is found that: First, nativism and naturalism genre which have the similar perspective about how the knowledge and potential of someone are the thing that must be keep and develop meanwhile others or society considered didn't have the capasity to develop the potential of the students.Secondly, emprisme side/genre thinks that the development of students maturity is defined by their enviroment (lingkungan). The third, convergence genre/side looked between the inside/ self potential that the students may have with the enviroment are the educational axiolgy process. Based on those theory, Educational Axiology which is developed in indonesia in line with the convergence theory. The other genre in a axiology perspective have not fully the legitimation "the utility” and “what are the benefits” of knowledge.